Morpho-Functional Characteristics Of Girls Specialized In NonTraditional Sports (Eurasian Scientific Herald, 2026)
In recent decades, the number of girls taking interest in non-traditional sports has grown considerably worldwide. While traditional sports have long held mainstream favor, this emerging trend has sparked significant scientific curiosity in the analysis of morphofunctional characteristics in female athletes breaking new ground in disciplines such as martial arts, powerlifting, skateboarding, sport climbing, rugby, and others. Understanding these parameters is essential for developing effective training protocols, optimizing performance, ensuring safety, and promoting holistic development among young female athletes.